Associations of nutritional status and dietary habits with the development of female infertility. A case–control study - Martín-Manchado, Laura; Moya-Yeste, Antonio Manuel; Sánchez-Sansegundo, Miriam; Hurtado-Sánchez, José Antonio; Gil-Miralles, Regina Andrea; Tuells, José; Zaragoza-Martí, Ana (Frontiers in Nutrition, 2024)
Introduction Female infertility is a multifactorial condition influenced by lifestyle and dietary factors. Understanding the relationship between nutritional status, dietary habits, and infertility could provide insights for targeted interventions. Methods A case-control study was conducted in health centers and hospitals in Alicante, Spain. The study included 60 infertile and 30 fertile women aged 18–40, selected through consecutive sampling. Data on body composition and dietary intake were collected and analyzed. Results Infertile women exhibited significantly lower muscle mass (p = 0.005) and larger hip circumference (p = 0.034) compared to fertile women. Additionally, a significant association was found between high red meat consumption and an increased risk of female infertility (p = 0.011). Discussion These results suggest that body composition and dietary habits, particularly muscle mass and red meat intake, play a key role in female fertility. Interventions aimed at improving muscle mass, reducing localized body fat, and limiting red meat consumption may enhance fertility outcomes. Further longitudinal research is needed to confirm these findings across diverse populations.